A review of power system planning and operational models for flexibility assessment in high solar energy penetration scenarios. (1st November 2020) - Emmanuel, Michael; Doubleday, Kate; Cakir, Burcin; Marković, Marija; Hodge, Bri-Mathias
Highlights: A summary of various metrics for evaluating power system flexibility is presented. Common power system models are reviewed to illustrate each model's outputs for flexibility assessment. Spatio-temporal resolutions/extents of power system models are discussed. An integrated model framework is proposed for the assessment of power system flexibility requirements. Abstract: This article reviews power system flexibility assessment, which is necessary to ensure both instantaneous stability and long-term security of supply under high penetrations of variable, uncertain, and asynchronous renewable energy resources, such as solar photovoltaics. This article reviews the concept of flexibility and summarizes metrics for evaluating power system flexibility, which is not yet available in the literature. Power system planning and operational models applicable for flexibility assessment, including net load analysis, capacity expansion, production cost, and dynamic models, are reviewed in a comprehensive literature survey, with a focus on high solar and other variable renewable energy penetrations. Each of these models applies different methodological approaches and feasibility criteria appropriate at different timescales. Finally, this article presents a conceptual integrated framework to combine these models for a holistic assessment of power system flexibility requirements across all timescales, from multiyear to sub-cycle.